The Effect of Wet Therapy on Blood Pressure Reduction in Hypertension Patients in the Clinic Bekam Lahtahzaan Karanganyar - Windarti; Noor Sari Aditiya; Dwi Lestari Palupi (LPPM Universitas Duta Bangsa Surakarta, 2019)
Hypertension and its incidence rate in Indonesia become a phenomenon. Based on the report of the development of the health status of the Indonesian people to the national and provincial levels. The purpose of this study to determine the effect of cupping therapy on the decrease in blood pressure in patients with hypertension. This research uses Quasi experiment method to find out whether or not the result of